Drivers of residual and tidal flow variability in the St. Lawrence fluvial estuary: Influence on tidal wave propagation. (15th February 2019) - Matte, Pascal; Secretan, Yves; Morin, Jean
Abstract: Accurately characterizing the spatiotemporal dynamics of residual and tidal flows is essential for understanding transport processes in tidal rivers and estuaries, as they directly affect salinity intrusion, water renewal capacity, sediment transport, and morphological evolution. This paper aims at characterizing the longitudinal and temporal variability of tidal discharges and currents in the St. Lawrence fluvial estuary (SLFE), under a wide range of river flow and tidal conditions. Tidal discharges and currents are reconstructed by cubature from nonstationary tidal analyses of water levels for a highly variable year, in terms of observed river flows, at 10 river cross-sections of the SLFE, distributed from the fluvial estuary entrance to the head of the tide. An analysis of the spatiotemporal variability in residual and tidal flows is hereby provided, with an emphasis on ebb-flood characteristics, residual currents, tidal constituent properties and tidal wave propagation characteristics at the intratidal, neap-spring and seasonal scales along the system. The main drivers and mechanisms responsible for this variability include (1) the system's hydrology and its associated watershed and meteorological characteristics, which dictate river flow intensity and seasonality, (2) the landward-travelling tides originating from the ocean, responsible for intratidal and tidal monthly variability in tides and currents, (3) nonlinear river-tide interactions, dissipating tidal energy, modulating tidal properties and inducing a surface level gradient, and (4) channel convergence and floodplain morphology, contributing to tidal asymmetry in horizontal and vertical tides. These factors ultimately influence tidal wave propagation and damping properties within estuaries, both longitudinally and at the neap-spring and seasonal scales. Highlights: Tidal discharges and currents are derived from nonstationary tidal analyses of water levels through continuity. Drivers of flow variability include hydrology, ocean tides, river-tide interactions, and channel and floodplain morphology. Flood velocities reduce in presence of tidal flats and respond the most strongly to changes in river flow during neap tides. Flow duration asymmetry is temporally lagged with respect to tidal duration asymmetry due to neap-spring storage effects. Fortnightly variations in tidal damping are driven by changes in friction closely linked to the neap-spring reversal of LW.